Kompas : Schilders uit Parijs 1945-1961. - Van Gindertael, Roger; Van Abbemuseum, Eindhoven (Eindhoven : Van Abbemuseum Eindhoven, 1961)
Alechinsky, Pierre ; Appel, Karel ; Bazaine, Jean ; Bissière, Roger ; Corneille ; Damian, Horia ; Dubuffet, Jean ; Estève, Maurice ; Fautrier, Jean ; Francis, Sam ; Hartung, Hans ; Herbin, Auguste ; Jorn, Asger ; Manessier, Alfred ; Messagier, Jean ; Michaux, Henri ; Mitchell, Joan ; Moser, Wilfrid ; Nallard, Louis ; Pignon, Edouard ; Poliakoff, Serge ; Riopelle, Jean-Paul ; Saura, Antonio ; Soulages, Pierre ; de Staël, Nicolas ; Tal-Coat, Pierre ; Tàpies, Antoni ; Vasarely, Victor ; van Velde, Bram ; Vieira da Silva, Maria Elena ; Wemaere, Pierre ; Wols
biog. [7 p.]
Frans
Nederlands
Kompas : schilders uit Parijs 1945-1961, Van Abbemuseum Eindhoven, 9 december1961 - 12 februari 1962
boek
Keywords: Parijs